The Importance of Energy Management in Hungary - Csipkés, Margit; Pusztai, László; Nagy, Lajos (International Journal of Engineering and Management Sciences, 2018)
One of the important elements of our everyday life is energy, but the amount of it is constantly decreasing, so it is advisable to include renewable energies in our energy management in addition to traditional energy sources. In the field of energy management, the use of renewable energies deserves attention because their share is increasing, although their percent is small. At present, Hungary and the European Union’s energy policy contain guidelines that aim to increase the utilization of renewable energy sources. These directives contribute to achieving environmental and climate protection goals, job creation, territorial and urban development, and the reduction of dependence on energy imports. In my article, I would like to present various calculations in the field of energy management as a result of the previously described information and I would like to explore the energy management contexts that have come to the fore when examining residential energy consumption